Comparing single‐feeding and multi‐feeding approaches for experimentally assessing trophic transfer of metals in fish. (29th November 2016) - Pouil, Simon; Warnau, Michel; Oberhänsli, François; Teyssié, Jean‐Louis; Bustamante, Paco; Metian, Marc
Abstract: Diet is an important pathway for metal uptake in marine organisms, and assimilation efficiency is one of the most relevant parameters to quantify trophic transfer of metals along aquatic food webs. The most commonly used method to estimate this parameter is pulse‐chase feeding using radiolabeled food. This approach is, however, based on several assumptions that are not always tested in an experimental context. The present study aimed to validate the approach by assessing single‐feeding and multiple‐feeding approaches, using a model species (the turbot Scophthalmus maximus ). Using the kinetic data obtained from the single‐feeding experiment, the reconstruction of a multi‐feeding experiment was tested for consistency with data provided by an actual multi‐feeding performed under the same experimental conditions. The results validated the single‐feeding approach. Environ Toxicol Chem 2017;36:1227–1234. © 2016 SETAC